2012
DOI: 10.1002/eji.201242741
|View full text |Cite
|
Sign up to set email alerts
|

Human Th17 subsets

Abstract: Since their discovery as a distinct T helper (Th) cell lineage, Th17 cells have been extensively investigated both in mice and in humans. These studies have identified factors involved in their differentiation and effector functions and have also revealed a high degree of flexibility that seems to be a characteristic of the Th17-cell lineage. In this review, we discuss recent studies addressing the heterogeneity of human Th17 cells, their differentiation requirements, their migratory capacities, and their role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
171
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(184 citation statements)
references
References 59 publications
8
171
0
5
Order By: Relevance
“…In the absence of HIV, mucosal Th17 cells produce several cytokines with a range of effector functions (28,38). Because HIV infection is associated with a dramatic reduction in the polyfunctional capacity of HIV-specific CD8 + T cells (39,40), we examined the effector functions of mucosal Th17 cells and their relationship with HIV-associated microbial translocation and immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of HIV, mucosal Th17 cells produce several cytokines with a range of effector functions (28,38). Because HIV infection is associated with a dramatic reduction in the polyfunctional capacity of HIV-specific CD8 + T cells (39,40), we examined the effector functions of mucosal Th17 cells and their relationship with HIV-associated microbial translocation and immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 was not only produced by Tr1 cells, but also promoted their differentiation (7). Recently, it also was shown that Staphylococcus aureus priming of naive human T cells generated IL-10-producing Th17 cells (regulatory Th17 cells), potentially as an intrinsic mechanism to suppress excessive inflammation in response to infection (8,9). Studies using in vivo infection with Toxoplasma gondii and Leishmania major revealed that Tbet 1 Th1 cells also secreted IL-10 (10, 11).…”
Section: Il-10: a Paradigm For Counterregulatory Cytokinesmentioning
confidence: 99%
“…Th1 lymphocytes express Tbet transcription factor and receptors CXCR3 [97], CCR6 [106], IL-18R [137] CCR5 [91], and some other (Table 1).…”
Section: T Cell Subpopulation: Differentiation and Plasticity Of Intementioning
confidence: 99%
“…Th2 lymphocytes express transcription factor Gata3 and receptors CD294 [54], CCR3, CCR4, CCR8, CRTH2, CD62L, CD30 (Table 1) [106]. At that, it should be specified that cytokine division into pro-and antiinflammatory is relative, and often the same cytokines occasionally have both pro-and anti-inflammatory activity, depending on a situation, such as IL-6 and IL-4.…”
Section: T Cell Subpopulation: Differentiation and Plasticity Of Intementioning
confidence: 99%
See 1 more Smart Citation